2014
DOI: 10.1371/journal.pone.0108862
|View full text |Cite
|
Sign up to set email alerts
|

Association of Angiopoietin-2 with Renal Outcome in Chronic Kidney Disease

Abstract: BackgroundThe pathophysiological mechanisms of renal function progression in chronic kidney disease (CKD) have still not been completely explored. In addition to well-known traditional risk factors, non-traditional risk factors, such as endothelial dysfunction, have gradually attracted physicians' attention. Angiopoietin-2 (Ang-2) impairs endothelial function through preventing angiopoietin-1 from binding to Tie2 receptor. Whether Ang-2 is associated with renal function progression in CKD is unknown.MethodsThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 37 publications
1
36
1
Order By: Relevance
“…Consistent with their report [15], serum Angpt2 increased stepwisely with urine PCR, and this was inreversely correlated with eGFR in our patients with diabetic nephropathy. Our previous study suggested that serum Angpt2 level was an independent risk factor for adverse renal outcomes in patients with CKD stages 3-5 [16]. However, whether serum Angpt2 can predict rapid deterioration in renal function in patients with clinical diabetes mellitus has not been well-explored.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with their report [15], serum Angpt2 increased stepwisely with urine PCR, and this was inreversely correlated with eGFR in our patients with diabetic nephropathy. Our previous study suggested that serum Angpt2 level was an independent risk factor for adverse renal outcomes in patients with CKD stages 3-5 [16]. However, whether serum Angpt2 can predict rapid deterioration in renal function in patients with clinical diabetes mellitus has not been well-explored.…”
Section: Discussionmentioning
confidence: 99%
“…Ang-2 is supposed to reflect the amount of endothelial activation [32] and to predict the severity and outcome in critically ill patients or of illnesses like acute pancreatitis [32], CKD [15], or after cardiac surgery [33], in early stages of the medical conditions. These predictions were often linked to an deterioration of renal function [15, 32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CKD, dialysis patients or renal transplant recipients, the progressive decline in glomerular filtration rate (GFR) is often associated with a significant elevation in serum Ang-2 concentrations [9]. In a further study in CKD patients, the estimated GFR (eGFR) was inversely related to circulating Ang-2 concentrations and Ang-2 concentrations rose with advancing CKD stages [15]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These three methods are widely applied in industries that demand forecasting [15,25,6,7,20]. However, in the past three years, the LME model has been broadly applied in various fields, such as the timber industry [30], medicine [9,49], and ecology [31], and to identify crucial influential factors. In addition, numerous studies have established models for forecasting [38,46].…”
Section: Forecasting Methodologymentioning
confidence: 99%